Crisis management in municipality - Prebilič, Vladimir (Journal of comparative politics, 2022)
The state responded to the non-military form of endangering people's lives in accordance with the National Plan for Protection and Rescue in the Event of an Outbreak of an Infectious Disease or Human Pandemic. However, especially in the first wave, many shortcomings of such a plan became apparent in the implementation of tasks at the level of local communities. They reacted differently to the threat and relied on a high degree of self-initiative, due to the limited functioning of the Protection and Rescue System at the regional level. Weaknesses were analysed and then largely remedied at the start of the second wave, so the response was more coordinated and more effective. The article sheds more light on the upgrade in operation between the first and second waves of the COVID-19 epidemic in Slovenia through the prism of local self-government.
Keywords: Civil defense; Civilna zaščita; Covid-19; Crisis management; Epidemics; Epidemije; Krizno upravljanje; Local government; Lokalna samouprava; Municipalities; Občine; zaščita in reševanje